PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWAKELAS IV SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Syamsinar Syamsinar; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the students achievment of science SD Negeri 023 Sedinginan fourth graderes still low with an average value of 60,25 and minimum completenness criteria (KKM) science studies is 70. Between students, amounting to 20 people only 8 students who achieve classical KKM with 40,00%. This research is Classroom Action Research (CAR), wich aims to improve the student achievement of science studies class IV at SD Negeri 023 Sedinginan with implementation model cooperative learning type GI. Formulation of the problem: is the implementation of model cooperative learning type GI can improve students achievment of science studies at SD Negeri 023 Sedinginan. The research was conducted on march 17, 2015 to april 14, 2015 by 2 cycles. Subjects were students of SD Negeri 023 Sedinginan, totalling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. Activities of the teacher in the learning process in cycle of 53,57% and the second meeting improve to 71,42%. Cycle II firs meeting and the second meeting improve 85,71% and the second meeting improve to 96,42%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 57,14% and a second meeting improve to 67,85%. Cycle II first meeting improve 82,14% and the second meeting improve to 92,85%. Improving student learning outcomes, on the basis of scores of students the average value is 60.25 in the first cycle increased 69.75 with increase big as 15,78% second cycle increased to be 80,50 with increase big as 33,6%.. increase in the percentage of students learning classical completeness on the basis of a score of 60.25 increased to 69.75 in the first cycle, the second cycle increased to 80.5 Result in the class IV at SD Negeri 023 Sedinginan that the implementation of model cooperative learning type GI can improve students achievement of science studies at fourth graderes SD Negeri 023 Sedinginan.Key Word: Model Cooperatif Learning Type GI, Achievement of Science Studies